Notes on Starlike log-Harmonic Functions of Order alpha - Aydoğan, Seher Melike; Yavuz Duman, Emel; Owa, Shigeyoshi (My University, 2013)
For log-harmonic functions f(z) = zh(z)g(z) in the open unit disk U, two subclasses H∗ LH(α) and G∗ LH (α) of S∗ LH(α) consisting of all starlike log-harmonic functions of order α (0 ≤ α < 1) are considered. The object of the present paper is to discuss some coefficient inequalities for h(z) and g(z).
Keywords: Analytic; log-harmonic; starlike; coefficient inequality